Đáp án:
Giải thích các bước giải:
a, 48=16.3
=> $\frac{(-48)^3}{16^3}$ = $\frac{-16^3.3^3}{16^3}$ =-3^3 = -27
b, Mình mạnh dạn sửa đề thành 2 phân số nhân với nhau mới rút ra số đẹp đc ^^
($\frac{-13}{8}$ )$^{3}$ . ($\frac{-32}{13}$ )$^{4}$
$\frac{-(13)^3}{8^3}$ . $\frac{(-32)^4}{13^4}$
= - $\frac{(8.4)^4}{13.8^3}$= - $\frac{8^4.4^4}{13.8^3}$
= - $\frac{8.4^4}{13}$=2048/13( cũng k đẹp lắm)
c, ($\frac{9}{10}$ )$^{6}$ : ($\frac{17}{-20}$ )$^{6}$
= $\frac{9^6}{10^6}$ : $\frac{17^6}{(-20)^6}$
= $\frac{9^6}{10^6}$ . $\frac{(-20)^6}{17^6}$
= $\frac{{9^6}2^6}{17^6}$
hay mình nhầm gì k b???